Electrical and thermal properties of surface passivated carbon nanotube/polyvinylidene fluoride composites. Issue 3 (10th October 2018) - Ouyang, Yingxiu; Deng, Yongmao; Li, Dandan; Cai, Zhihong; Xu, Ruijie; Lei, Caihong; Lu, Shengguo
Abstract : The composites reported here were prepared through a melt‐rolling mixing process, in which surface passivated multi‐wall carbon nanotube and poly(vinylidene fluoride) were used as the filler and the matrix, respectively. X‐ray diffraction, precision inductance–capacitance–resistance, and laser flash thermal‐diffusivity analyses were employed to characterise the structural, electrical and thermal properties. Results indicate that through the surface passivation of carbon nanotubes, the electrical resistivities of the composites were greatly enhanced, while the thermal conductivities do not change significantly. The electrical properties were discussed in comparison with the Maxwell–Wagner polarisation, universal law, and Gerhardt's method.